THE INFLUENCE OF ORGANIZATIONAL CULTURE, PRINCIPAL LEADERSHIP AND SCHOOL ENVIRONMENT ON ORGANIZATIONAL COMMITMENT IN DISTRICT HIGH SCHOOLS JUANG CITY BIREUEN REGENCY - Basri, Hasan; Kamaruddin, Kamaruddin (IndOmera, 2020)
The study was conducted on teachers of state high schools in Juang City District of Bireuen Regency, with the aim being to determine the effect; 1). organizational culture towards the organizational commitment of teachers, 2) leadership of the school principal towards the commitment of teacher organizations, 3). the school environment towards the organizational commitment of teachers, and 4). organizational culture, school principal's leadership and school environment towards the teacher's organizational commitment. This research is in the form of a quantitative study with a survey of 118 high school civil servant teachers in Juang City District, Bireuen Regency, by collecting data through a questionnaire. And the data analysis method with the path analysis approach. The results of the study showed that it was proven; 1). the influence of organizational culture factors on organizational commitment, at 10.12 percent. 2). 30.17 percent influence the Principal's Leadership on Organizational Commitment, 3). the influence of the School Environment on organizational commitment of 2.92 percent, and 4). Through the coefficient of determination explains that the contribution of factors Organizational Culture, Principal Leadership, and School Environment to the Commitment of teacher organizations by 43.2 percent. While the rest of the role of variables not examined was 34.8% which were assumed to be factors such as compensation, organizational climate, work facilities, Education and Training, etc